2006
DOI: 10.1002/pmic.200500257
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of hepatocellular carcinoma by laser capture microdissection

Abstract: Hepatocellular carcinoma (HCC) is one of the most frequent visceral neoplasia worldwide and is a multifactorial and multistage pathogenesis that finally leads to the deregulation of cell homeostasis. Laser capture microdissection (LCM) may allow a more ready identification of differences in protein expression in selected cell types or areas of tissue, and microscopic regions as small as 3-5 microm in diameter can be sampled. Here we applied the LCM to the proteomic study of hepatitis B-related HCC and surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…In the present study, we also found that the WBC was higher in the PC + DM group than that in the common type 2 DM group (p = 0.002), indicating the presence of inflammation, which may be responsible for the lower APO-A1 concentration in PC + DM. The reduction of APO-A1 was also shown in other types of cancer such as ovarian and liver cancer [39,40]. These results are in accordance with our finding that APO-A1 is an independent risk factor for differentiating PC + DM from common type 2 diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we also found that the WBC was higher in the PC + DM group than that in the common type 2 DM group (p = 0.002), indicating the presence of inflammation, which may be responsible for the lower APO-A1 concentration in PC + DM. The reduction of APO-A1 was also shown in other types of cancer such as ovarian and liver cancer [39,40]. These results are in accordance with our finding that APO-A1 is an independent risk factor for differentiating PC + DM from common type 2 diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, MS is a powerful tool for resolving the complexity of cancer signaling pathways. With regard to HCC, qualitative proteomics has been performed on resected tumor material (12), laser-capture microdissected material from tissue sections (13,14), and primary hepatocytes or serum derived from patients (15,16). These studies (17,18) identified HCC biomarkers such as glutamine synthetase and heat shock protein 70 (Hsp70) that are currently in use for diagnosis (19,20).…”
mentioning
confidence: 99%
“…Previous studies have reported the diagnostic value of ApoA-1 and proApolipoprotein A1 (the precursor of ApoA-1) in tumor diagnosis. Decreased levels of ApoA-1 were found in a variety of cancers [18][19][20][21][22][23], but pro-ApoA-1 increased in breast cancer [24]. Marchi et al found that pro-ApoA-1 significantly increased (p<0.05) in lung cancer patients with brain metastases [25].…”
Section: Discussionmentioning
confidence: 99%